Evaluating Principals’ Administrative Planning Skills in Public Senior Secondary Schools in Ethiope East, Delta State - Ovie , Nuvie Nunu Aruekure Brown; Eregie, Augustine Edomwonyi; Ugbenu, Avwerosuo Rachel (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Background: Effective school administration depends largely on the planning ability of principals to manage financial, physical, and strategic aspects of educational institutions. In many public secondary schools, the level of administrative planning directly influences teaching quality, infrastructure condition, and long-term school improvement. Aim: The study was conducted to evaluate the administrative planning skills of principals in public senior secondary schools in Ethiope East Local Government Area of Delta State. It focused specifically on assessing their competence in financial planning, physical facilities maintenance planning, and strategic planning. Method: A descriptive survey design was used to collect data from 100 randomly selected teachers using a validated instrument titled Assessment of Principals’ Administrative Skills on Educational Planning Questionnaire (APASEPQ). The data were analysed using frequency counts, percentages, and mean scores to determine the levels and dimensions of principals’ administrative planning skills. Results and Discussion: Findings revealed that principals demonstrated a high level of competence in physical facilities maintenance and strategic planning, indicating effective supervision, stakeholder engagement, and goal-oriented leadership. However, their financial planning skills were only moderate, reflecting gaps in transparency, accountability, and detailed financial control. Overall, 68% of teachers rated their principals’ administrative planning skills as high, confirming that most school leaders are performing effectively in managing school operations but still require improved financial management capacity. Conclusion: The study concludes that principals in Ethiope East Local Government Area possess generally strong administrative planning abilities that positively influence school functioning. Nevertheless, their limited financial planning competence underscores the need for continuous professional development in budgeting, expenditure tracking, and accountability practices. Strengthening these areas will enhance principals’ overall effectiveness and contribute to sustained educational quality and institutional improvement across public senior secondary schools in Delta State.